2010
DOI: 10.1097/aln.0b013e3181ca31d9
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for the Ongoing Brain Activation by Enhanced Dynorphinergic System in the Spinal Cord under Inflammatory Noxious Stimuli

Abstract: These findings indicate that spinally released dynorphin A (1-17) by noxious stimuli leads to the direct activation of ascending pain transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Reports of specific drivers of neuromodulators (e.g., dyorphin) have been employed in knockout vs. control mice in response to inflammatory stimuli (complete Freunds adjuvant) (Taketa et al, 2010); no activation was observed in regions such as the cingulate, somatosensory and insular cortices or thalamus in prodynorphin knockout mice. Other fMRI visceral pain studies have included those in acute pancreatitis (see Figure 3A) (Westlund et al, 2009), investigating the effects of a mu agonist (morphine) and mu antagonist (naloxone) and following a peripheral pain stimulus (intraplantar formalin).…”
Section: Preclinical Functional Imaging Of Painmentioning
confidence: 99%
“…Reports of specific drivers of neuromodulators (e.g., dyorphin) have been employed in knockout vs. control mice in response to inflammatory stimuli (complete Freunds adjuvant) (Taketa et al, 2010); no activation was observed in regions such as the cingulate, somatosensory and insular cortices or thalamus in prodynorphin knockout mice. Other fMRI visceral pain studies have included those in acute pancreatitis (see Figure 3A) (Westlund et al, 2009), investigating the effects of a mu agonist (morphine) and mu antagonist (naloxone) and following a peripheral pain stimulus (intraplantar formalin).…”
Section: Preclinical Functional Imaging Of Painmentioning
confidence: 99%
“…Both KOR and PDYN KO mice are viable, with reported phenotypic effects on neural function such as enhancement of pain perception. 1,[27][28][29] Vascular phenotype, however, has not been investigated in either of these KO mice. Both KOR and PDYN KO mice showed a greater density of CD31 ϩ vessels in the periphery of EϪ10.5 embryonic brains (Figure 6B-C).…”
Section: Kor or Dynorphin Ko Mice Show Increased Vascular Formation Imentioning
confidence: 99%
“…Prodynorphin (PDYN) gene-KO mice (The Jackson Laboratory), 27,28 KOR gene-KO mice (The Jackson Laboratory), 29 or C57BL/6J mice (CLEA Japan Inc) were used. Mice were allowed to mate naturally at night.…”
Section: Micementioning
confidence: 99%
“…Under these circumstances, 'ON'-RVM neurons do not respond to inhibitory signals from PAG, whereas they are highly stimulated by ascending inputs (Figure 4) 86,92,93 that release glutamate, SP and dynorphin over thalamic and brainstem neurons including 'ON'-RVM cells. [84][85][86][87][88][89][90][91][92][93][94][95][96] In summary, all these neurotransmitters released by nociceptive ascending neurons over 'ON'-RVM neurons cause their hyperexcitability (Figure 4). 97 Neuropathic and inflammatory pain also causes changes in PAG neurons.…”
Section: Molecular Neuroplasticity Of the Descending Inhibitory Pain mentioning
confidence: 99%